2006
DOI: 10.1080/02652030600699320
|View full text |Cite
|
Sign up to set email alerts
|

Chemical contamination of free-range eggs from Belgium

Abstract: The elements manganese, cobalt, nickel, copper, zinc, arsenic, selenium, molybdenum, cadmium, antimony, thallium, lead and mercury, and selected persistent organochlorine compounds (dioxins, marker and dioxin-like polychlorinated biphenyls, dichlorodiphenyltricholroethane (DDT) and metabolites as well as other chlorinated pesticides) were analysed in Belgian free-range eggs obtained from hens of private owners and of commercial farms. It was found that eggs from private owners were more contaminated than eggs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 28 publications
1
48
6
Order By: Relevance
“…Concentrations of heavy metals found in the eggs of our study (Table 3) were far below the toxic limits reported in the literature [30]. Other researchers have found increased concentrations of heavy metals and organochlorine compounds in eggs from hens kept in free-range systems [31].…”
Section: Discussionmentioning
confidence: 64%
“…Concentrations of heavy metals found in the eggs of our study (Table 3) were far below the toxic limits reported in the literature [30]. Other researchers have found increased concentrations of heavy metals and organochlorine compounds in eggs from hens kept in free-range systems [31].…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand Rawn et al (2012) and Luzardo et al (2013) have found similar results in the concentration and frequency of detected OCPs, with only small differences among examined groups. These higher concentrations of OCPs in farm produced eggs may be due to eating soil and soil's creatures (worms and other insects) in farms that do not use barn floor, as they are more exposed to environmental pollutants than those are caged or in outdoor home produced with barn floor, where the possibility of eating soil does not exist (Van Overmeire et al, 2006;Windal et al, 2009). Table 2 showed that the egg-related calculated average daily intake of pesticides for people living in Sharkia Province is extremely lower than the ADI established by the WHO for these contaminants ( JMPR) and the level of exposure of this population through this food is lower than estimates recently published for other populations (Darnerud et al, 2006;Van Overmeire et al, 2006;Polder et al, 2010;Luzardo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…(2) Coleman et al, 1992Gerber et al, 2009. (3) Hidiroglou andShearer, 1976;Coleman et al, 1992;Jorhem and Sundström, 1993;Blanco-Penedo et al, 2006;Gerber et al, 2009. From three studies (Leblanc et al, 2005;Van Overmeire et al, 2006;Gerber et al, 2009), 0.3 mg Mn/kg egg could be derived as the highest concentration for eggs. For milk, rather low manganese levels (up to 0.1 mg/L) are reported in two studies (Santos et al, 2004;Leblanc et al, 2005).…”
Section: Manganese Deposition Studiesmentioning
confidence: 99%